Studi Etnomatematika Pada Budaya Masyarakat Larantuka - Ni Ketut Artanti Agustini; Samuel Igo Leton; Aloysius Joakim Fernandez (Program Studi Pendidikan Matematika Universitas Katolik Widya Mandira, 2019)
The environment can become a source of learning in a process of mathematical learning related to the real world. One source learning in the environment is cultural. Mathematical lessons that studied educated participants at school are sometimes different to important transatic problems that encountered in everyday life, makes it more difficult learning participants linking the links of furatic concepts that are formal with issues of culture. Etnomathematics connects cultures with mathematics learning. The purpose of this research is to obtain the description of the value of the impostor’s value and growing up to the cultural society of Waibalun. This type of research is a qualitative research with the Etnographic design. Data collection by observation, interviews and documentation. The subject in this study is three person taken Purposive against public figures who learn and understand well about indigenous homes. The object of this research is the Waibalun indigenous home. The results of data analysis show that a) Etnomathematical activity in the process of making Waibalun indigenous homes, that is measuring, counting and designing; b) The mathematical values were found in the Waibalun indigenous home consist of, the angle, rectangle, triangle, trapezium, tube and reflections.